Peripheral Nerve Field Stimulation Therapy for Patients With Thoracic Pain: A Prospective Study. Issue 7 (4th July 2016) - Mitchell, Bruce; Verrills, Paul; Vivian, David; DuToit, Neels; Barnard, Adele; Sinclair, Chantelle
Abstract : Objective: Relative to the number of patients suffering chronic lumbar and cervical pain, fewer patients suffer persistent thoracic pain. Consequently there is less literature, with smaller sample sizes, reporting treatment of this cohort. Here, we assess peripheral nerve field stimulation (PNfS) as a potential treatment for chronic thoracic pain. Materials and Methods: This study included 20 consecutive chronic thoracic pain sufferers that responded successfully to PNfS trial. The patients were subsequently implanted with permanent eight‐contact electrode linear percutaneous leads within their major area of pain. Patients were followed up at 12 months for outcome reporting. All 20 patients were considered in the statistical analysis, despite removal of three devices prior to follow up. Results: The average baseline pre‐treatment Numerical Pain Rating Scale (NPRS) score was 7.75 ± 1.4. Following PNfS, the mean NPRS score was 2.25 ±2.14, reflecting a significant average improvement of 5.5 ± 3.31. Three patients were explanted prior to follow up: the first gained excellent thoracic pain relief but pain at the Implantable Pulse Generator (IPG) site could not be overcome, the second achieved excellent pain relief but the PNfS was removed due to recurrent infection and in the final instance, the intervention offered only poor relief and the device removed. Conclusion: PNfS is an effective intervention for intractable disabling thoracic pain, offering sustained and worthwhile pain relief, for the overwhelming majority of the cohort. This may be especially true when considering a combined treatment approach of PNfS and analgesic use to manage remnant pain.